THE EFFECT OF NIVOLUMAB IN PEDIATRIC MALIGNANT TUMORS: A SINGLE CENTER EXPERIENCE WITH EIGHT PATIENTS - Veysel GOK (Elsevier, 2021)
Objective: The programmed cell death 1 (PD-1) receptor is an immune checkpoint receptor expressed by activated T cells. PD-1 inhibits the immune system by binding to its ligands expressed on tumor cells. Nivolumab and pembrolizumab are some of the monoclonal antibodies that inhibit the PD-1. We present our experience with eight cases which were treated with nivolumab for different malignant diseases in our clinic. Methodology: A total of eight patients (5 girls, 3 boys) aged between 4 and 16 years were treated with nivolumab at 3mg/kg/dose approximately twice a week in Erciyes University Pediatric Hematology clinic between 2019-2021. Nivolumab treatments of seven patients were given median 11 (4-32) doses and discontinued due to progression at a median 6 months (2-17 months). Results: Four patients were diagnosed with miss match repair syndrome in addition to their malignant disease. Non-Hodgkin lymphoma (two with T-cell and one with histiocyte-rich B-cell) in three patients, brain tumor (pons glioma, midline glioma, glioblastoma multiforme) in three patients, germ cell tumor (yolk salk, immature teratoma) in two patients, one patient had colon adenocarcinoma in addition to brain tumor. Except for nausea in a patient, no drug-related side effect was observed in patients. Conclusion: Nivolumab was well tolerated in patients with CMMRD syndrome with some transient partial responses. There is a risk of developing secondary cancer in patients with CMMRD syndrome. Further studies are needed due to the limited use in children.